Competências docentes e interdisciplinaridade no processo de ensino-aprendizagem em Administração - Christiano, Cristina Alves (2014)
This work is encouraged by the need that exists currently to motivate students in upper level management in the teaching-learning process. Teaching in higher education is faced countless times, with students eager for knowledge, being the educator adapt their methodology to make it happen in a pleasant coexistence and learning for both parties. Should be a priority goal of teaching and also make the School a suitable environment for education. The practice of teacher education as perceived by the instrument of transformation allows the same to be aware of their need for ongoing training and professional knowledge. The teacher should use the research to develop the habit of their learning and the improvement of skills aiming at interdisciplinarity, developing strategic activities and dynamic actions that challenge or enable the development of mental operations using the integration of disciplines to better match their praxis. The teacher is challenged to act when a new perspective on the teaching- learning process, may encounter obstacles and in the case of the use of interdisciplinarity with the breakup of the traditional form established throughout the history of education. However, to the extent that the teacher gets the awareness of the need to adapt current requirements, your task is facilitated by allowing the same self evaluate ministry from their classes and to perfect it in favor of the student, not to mention learning the upper level is related to the labor market, which is considered a major challenge for teachers as well as for higher Education Institutions ( HEIs ).We sought theoretical framework based on authors who discuss this topic,namely. The study is characterized as qualitative, with emphasis on narrative writing, allowing the researcher knowledge about the object of research. To collect the data we used the instrument: questionnaire. This data analysis was guided by the technique of content analysis, supported by Bardin (1994). It was found from the study revealed that respondents , on their skills teachers reasoned discourse among other theorists Philippe Perrenoud, who understands that the development of critical skills training allows professionals with systems thinking allowing complex problems to be analyzed and solved.